2017
DOI: 10.1111/1365-2435.12886
|View full text |Cite
|
Sign up to set email alerts
|

Begging blue tit nestlings discriminate between the odour of familiar and unfamiliar conspecifics

Abstract: Summary Offspring often solicit, and compete for, limited parental care by elaborate begging behaviour. Kin selection theory predicts that competing offspring should modify the intensity of their begging depending on the degree of relatedness to their nest‐ or litter‐mates. Empirical evidence in birds, which are a key model in the study of parent‐offspring interactions, indeed indicates that a lower level of relatedness between offspring in the nest correlates with more intense begging (i.e. more ‘selfish’ b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 75 publications
0
16
0
Order By: Relevance
“…Beecher, 1988;McDonald & Wright, 2011), and visual cues may also be involved (Palestis & Burger, 1999). Recognition may also be based on olfaction (Krause et al, 2012;Rossi et al, 2017). A study of cooperatively breeding long-tailed tits (Aegithalos caudatus) found that their behaviour was consistent with recognition learned by association, and that these birds can discriminate between kin and non-kin based on individual-specific characteristics of contact calls.…”
Section: (5) Kin Recognition and Rejection Of Non-kinmentioning
confidence: 99%
“…Beecher, 1988;McDonald & Wright, 2011), and visual cues may also be involved (Palestis & Burger, 1999). Recognition may also be based on olfaction (Krause et al, 2012;Rossi et al, 2017). A study of cooperatively breeding long-tailed tits (Aegithalos caudatus) found that their behaviour was consistent with recognition learned by association, and that these birds can discriminate between kin and non-kin based on individual-specific characteristics of contact calls.…”
Section: (5) Kin Recognition and Rejection Of Non-kinmentioning
confidence: 99%
“…For the nest scent recognition experiment, we tested nestlings at 1 day of age and found no difference in response between orange scent and water, whereas for the parent scent recognition experiment, we tested nestlings at 2 days of age and found a change in response depending on the scent type. Similar experiments on zebra finches performed on the day of hatch (Caspers et al, ) or 1 day after hatch (Caspers et al, ) found significant effects in response to odour type, while an experiment on blue tits, which also found significant effects in response to odour type, tested nestlings at 7 days post‐hatch (Rossi et al, ). As our experiment was the first such experiment on tree swallows, however, we cannot rule out that olfactory development may be slower in nestling tree swallows than zebra finches, and therefore, they may be more responsive to odour stimuli when they are older.…”
Section: Discussionmentioning
confidence: 78%
“…Cross‐fostering nestlings (Caspers & Krause, ) and eggs (Caspers, Hoffman, Kohlmeier, Krüger, & Krause, ) showed that nestlings learned the odour of their nest during a short time period around hatching. Nestling zebra finches also begged longer to odours of a familiar than unfamiliar adult (Caspers et al, ), whereas nestling blue tits ( Cyanistes caeruleus ) begged longer and more intensely to odours of unfamiliar than familiar nestlings (Rossi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In several procellariform species, young chicks seem to demonstrate odor recognition (Cunningham, Buskirk, Bonadonna, Weimerskirch, & Nevitt, 2003;De Leon, Mínguez, & Belliure, 2003). Within the same family as chickadees (Paridae), blue tits have also been shown to exhibit odor recognition at the nestling stage (Rossi et al, 2017). Within the same family as chickadees (Paridae), blue tits have also been shown to exhibit odor recognition at the nestling stage (Rossi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Preference for extraneous odors has been found to develop during the incubation period in chickens (Sneddon, Hadden, & Hepper, 1998) while preferences for parental odors may be determined earlier in egg development in zebra finches . Within the same family as chickadees (Paridae), blue tits have also been shown to exhibit odor recognition at the nestling stage (Rossi et al, 2017). While more work needs to be done in this area, the possibility that odor preferences are formed during development in chickadees could facilitate its function in reproductive isolation if individuals learn preferences from parental odors in pure-species nests.…”
Section: Discussionmentioning
confidence: 99%